Keanekaragaman Serangga Hama Pada Kawasan Agrowisata Universitas Muhammadiyah Luwuk Desa Lontos Kecamatan Luwuk Timur Kabupaten Banggai - Anggo, Sulasmi; Muzain, Dina; Karim, Wahyudin Abdul; Lige, Firga Nabila (Jurnal Biologi Babasal, 2022)
Abstract: Insect pests act as damage to plants, currently there is no research on insect pests in agrotourism areas. This study aims to determine the diversity index of insect pests found in the agrotourism area of ??Muhammadiyah University Luwuk, Lontos Village, East Luwuk District, Banggai Regency. Held in July 2022.The research method used is descriptive quantitative method. Research design of yellow trap trapping and handpicking. Installation of yellow trap traps on plants attacked by insect pests, namely passion fruit, cassava, papaya, pomegranate, guava, chili, banana, kale, purple shoot ornamental plants. The sampling technique was random sampling method. The data taken are types of insects that have the potential as pests in agro-tourism areas. Supporting data measured are environmental factors, air temperature, humidity, wind speed. Sample identification was carried out in the direct field and in the biology education laboratory, FKIP Muhammadiyah Luwuk University. The results showed the insect pest diversity index H'= 1.87, in the medium category. This means that the ecosystem in the stability of agro-tourism in species has reached a higher climax in a community, so that it can be a moderate ecosystem and affect environmental factors to maintain its life. The average temperature is 28.6 0C, the average humidity is 75.4%, the wind speed is 8.8 knots. The results obtained were 88 individuals belonging to 13 species.